WorldFish, IDEA project Bangladesh & Pro-WEFI - Adam, Rahma; Rajaratnam, Surendran (WorldFish, 2022)
Presentation from a a training workshop on Project Level Women's Empowerment in Fisheries and Aquaculture Index (Pro-WEFI) tool for validation in increasing income, diversifying diets, and empowering women in Bangladesh (IDEA) project sites, Bangladesh.